Theoretical considerations in reducing risk for cardiovascular disease: implications for nursing practice - Gholizadeh, L.; Davidson, Patricia; Salamonson, Y.; Worrall-Carter, L. (Blackwell Publishing, 2010)
Aims and objectives. This article describes the theoretical foundation of risk perception as a key component of changing deleterious health behaviours associated with cardiovascular disease (CVD). Furthermore, perception in increasing cardiovascular risk-reducing behaviours in a socio-cultural framework is discussed, and an empirical development conceptual model presented. Background. Perception of risk is strongly linked with health-seeking behaviours. Understanding how to reduce risk and maximise cardiovascular health is an increasing focus of clinicians, researchers and policy makers. Increasing cultural diversity in contemporary society means that nurses need to develop and evaluate interventions in this context. Design. An integrative literature review. Method. An integrative literature review method was used to assess conceptual models relating to risk perception of developing CVD. On the basis of the findings, a model was developed to inform future intervention studies, considering individual, social and cultural factors.Discussion. Studies examining CVD and health behaviours report that there is limited concordance between actual and perceived risk in people with CVD. This mismatch risk likely impedes the adoption of risk-reducing behaviours. Conclusion. There is a critical need to develop interventions for enhancing an accurate perception of CVD risk considering not only individual but social factors. Relevance to clinical practice. There is limited correlation between knowledge and behaviours, and health behaviours are influenced by individual, social and cultural factors. Appraising the congruence between actual and perceived risk is an important step in developing effective care plans to reduce cardiovascular risk.